Algeplan como ferramenta auxiliar no ensino de álgebra do 9º ano - Marcellino, Fábio Furtado (Brasil, 2025)
The article "ALGEPLAN AS AN AUXILIARY TOOL IN TEACHING 9TH GRADE ALGEBRA" presents Algeplan® as a didactic resource for teaching algebra in the 9th grade of elementary school. The study highlights students' difficulties with traditional algebra and proposes the use of a manipulable kit composed of physical pieces that represent variables and mathematical operations. • Introduction: Discusses the importance of teaching algebra and the need for methods that facilitate students’ understanding, citing guidelines from the Common National Curriculum Base (BNCC). • Difficulties in Teaching Algebra: Points out students' lack of motivation and the impact of traditional teaching focused on memorization. • Use of Algeplan: The kit consists of geometric pieces that help visualize and solve first and second-degree equations, allowing concrete interaction with abstract concepts. • Applications: ◦ Solving quadratic equations by organizing the pieces. ◦ Finding roots and factoring polynomials visually. ◦ Using negative pieces to represent negative numbers. ◦ Representing perfect square trinomials. • Conclusion: Algeplan is an effective tool that makes algebra more accessible and engaging, reducing students' anxiety and promoting more intuitive learning. The article reinforces that the use of Algeplan can be integrated into traditional classes to increase engagement and facilitate the understanding of algebraic concepts.